The new financial regulation in Basel III and monetary policy: a macroprudential approach - Rubio, Margarita; Carrasco-Gallego, José A. (Elsevier, 2016)
The aim of this paper is to study the interaction between Basel I, II and III regulations with monetary policy. In order to do that, we use a dynamic stochastic general equilibrium (DSGE) model with a housing market, banks, borrowers, and savers. Results show that monetary policy needs to be more aggressive when the capital requirement ratio (CRR) increases because the money multiplier decreases. However, this policy combination brings a more stable economic and financial system. We also analyze the optimal way to implement the countercyclical capital buffer stated by Basel III. We propose that the CRR follows a rule that responds to deviations of credit from its steady state. We find that the optimal implementation of this macroprudential rule together with monetary policy brings extra financial stability with respect to Basel I and II.